1986
DOI: 10.2307/3576850
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of the Involvement of the recA, recB, recC, recF, recJ, recN, lexA, radA, radB, uvrD, and umuC Genes in the Repair of X-Ray-Induced DNA Double-Strand Breaks in Escherichia coli

Abstract: Isogenic Escherichia coli strains carrying single DNA-repair mutations were compared for their capacity for (i) the repair of X-ray-induced DNA double-strand breaks (DSB) as measured using neutral sucrose gradients; (ii) medium-dependent resistance, i.e., a recA-dependent X-ray survival phenomenon that correlates closely with the capacity for repairing DSB; and (iii) the growth medium-dependent, recA-dependent repair of X-ray-induced DNA single-strand breaks (SSB) as measured using alkaline sucrose gradients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 45 publications
4
77
0
Order By: Relevance
“…The efficiency of DSB repair in wild-type cells is dramatically reduced by recN mutations (Picksley et al, 1984;Sargentini and Smith, 1986). Consistent with our proposal that RDR is involved in DSB repair, we have found that a recN mutation greatly reduces RDR in rec + sbc + cells.…”
Section: Possible Roles Of Rdr In Dsb Repairsupporting
confidence: 91%
“…The efficiency of DSB repair in wild-type cells is dramatically reduced by recN mutations (Picksley et al, 1984;Sargentini and Smith, 1986). Consistent with our proposal that RDR is involved in DSB repair, we have found that a recN mutation greatly reduces RDR in rec + sbc + cells.…”
Section: Possible Roles Of Rdr In Dsb Repairsupporting
confidence: 91%
“…We propose that the reason for this is the inefficient repair of double-strand breaks in strains deficient for recB, recC, or both (34 (48) and that recD cells are even more resistant than wild-type cells to gamma irradiation (21) are in accord with the proposal that recBC-dependent unwinding of duplex DNA ends initiates efficient recombination repair at doublestrand breaks.…”
Section: Discussionmentioning
confidence: 69%
“…Unlike other members of the RecF pathway, recN mutants are quite sensitive to ionizing radiation or mitomycin C, and the repair of multiple, site-specific DSBs does not occur in the absence of RecN (8,12,13). The recN gene is also required for the suppression of chromosomal rearrangements and deletions (12) during the repair of a single DSB.…”
mentioning
confidence: 99%